2006
DOI: 10.1017/s1049023x00003629
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Health Education and Training: A Pilot Questionnaire to Understand Current Status

Abstract: In October 2004, a World Association for Disaster and Emergency Medicine (WADEM) Seminar was convened in Brusselsby the Education Committee to discuss Disaster Education and Training. During this seminar, it became apparent that there was no single tool available to assess knowledge, skills, and resources within this field. Therefore, a tool was administered to 50 of the delegates to assess if the tool would facilitate information-sharing and curriculum development in disaster health education.The WADEM Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Consequently, a training curriculum contextualized to the local environmental and socioeconomic milieu was developed [19]. At the same time, because crises can span geographic and political regions, the program is also consistent with international educational and disaster medicine standards [20,21]. The aim of the current study was to evaluate the efficacy of this curriculum in improving the knowledge of Saudi Arabian medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a training curriculum contextualized to the local environmental and socioeconomic milieu was developed [19]. At the same time, because crises can span geographic and political regions, the program is also consistent with international educational and disaster medicine standards [20,21]. The aim of the current study was to evaluate the efficacy of this curriculum in improving the knowledge of Saudi Arabian medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Murray et al 8 reported that a pilot questionnaire should be developed to answer questions regarding present practices in disaster education and training, and the questionnaire should be updated annually. The framework of our questionnaire extracted information on curriculum development in fire-evacuation training.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate patients consisted of one with hemorrhagic shock and one with a tension pneu-educated and trained and what kinds of courses should be provided. 2 Core clinical competencies for healthcare practitioners include the demonstration of proficiency in the use of triage systems in disasters and the application of clinical knowledge and skills in the management of injuries. 3 The use of human patient simulators in health education allows healthcare providers to practice skills without risk to patients/subjects, providing a natural framework for the integration of basic and clinical science.…”
Section: Scenariosmentioning
confidence: 99%